Projecting Britain at war : the national character in British World War II films - Havardi, Jeremy (McFarland & Company, Inc., Publishers, 2014)
"This detailed chronological analysis of British World War II movies from 1939 until the present explores how recognizable stereotypes of British national character were projected and how the times in which a film was made shaped its perceptions"--